Neutrophil extracellular traps in cancer: not only catching microbes - Livia Ronchetti; Nouha Setti Boubaker; Maddalena Barba; Patrizia Vici; Aymone Gurtner; Giulia Piaggio (Journal of Experimental & Clinical Cancer Research, 2021)
Abstract Neutrophils are the most abundant type of white blood cells circulating throughout the bloodstream and are often considered the frontline defenders in innate immunity. However, neutrophils are increasingly being recognized as having an important role in tumorigenesis and carcinogenesis due to their aberrant activation by molecules released into the tumor microenvironment. One defensive response of neutrophils that is aberrantly triggered during the neoplastic process is called NETosis, where activated neutrophils expel their DNA and intracellular contents in a web-like structure known as a neutrophil extracellular trap (NET). In cancer, NETosis has been linked to increased disease progression, metastasis, and complications such as venous thromboembolism. NET structures released by neutrophils can also serve as a scaffold for clot formation, shining new light on the role of neutrophils and NETosis in coagulation-mediated diseases. Here, we review current available knowledge regarding NET and the related NETosis process in cancer patients, with an emphasis on pre-clinical and clinical data fostering the identification and validation of biomarkers of NET with a predictive/prognostic role in cancer patients treated with immunotherapy agents. NETosis biomarkers, e.g., citH3, may integrate correlates of immunogenicity currently available (e.g., PD-L1 expression, TMB, TILs) and help select the subsets of patients who may most benefit from the use of the therapeutic weapons under discussion.